Presentation is loading. Please wait.

Presentation is loading. Please wait.

11.3: Geometric Sequences & Series

Similar presentations


Presentation on theme: "11.3: Geometric Sequences & Series"— Presentation transcript:

1 11.3: Geometric Sequences & Series

2 nth Term of an Geometric Sequence:
an = a1r(n – 1)

3 nth Term of an Geometric Sequence:
an = a1r(n – 1) Ex. 2 Determine the following: a) Find the eighth term of a geometric sequence for which a1 = -3 and r = -2.

4 nth Term of an Geometric Sequence:
an = a1r(n – 1) Ex. 2 Determine the following: a) Find the eighth term of a geometric sequence for which a1 = -3 and r = -2.

5 nth Term of an Geometric Sequence:
an = a1r(n – 1) Ex. 2 Determine the following: a) Find the eighth term of a geometric sequence for which a1 = -3 and r = -2. a8 = a1r(8 – 1)

6 nth Term of an Geometric Sequence:
an = a1r(n – 1) Ex. 2 Determine the following: a) Find the eighth term of a geometric sequence for which a1 = -3 and r = -2. a8 = a1r(8 – 1) a8 = (-3)r(8 – 1)

7 nth Term of an Geometric Sequence:
an = a1r(n – 1) Ex. 2 Determine the following: a) Find the eighth term of a geometric sequence for which a1 = -3 and r = -2. a8 = a1r(8 – 1) a8 = (-3)r(8 – 1) a8 = (-3)(-2)(8 – 1)

8 nth Term of an Geometric Sequence:
an = a1r(n – 1) Ex. 2 Determine the following: a) Find the eighth term of a geometric sequence for which a1 = -3 and r = -2. a8 = a1r(8 – 1) a8 = (-3)r(8 – 1) a8 = (-3)(-2)(8 – 1) a8 = (-3)(-27)

9 nth Term of an Geometric Sequence:
an = a1r(n – 1) Ex. 2 Determine the following: a) Find the eighth term of a geometric sequence for which a1 = -3 and r = -2. a8 = a1r(8 – 1) a8 = (-3)r(8 – 1) a8 = (-3)(-2)(8 – 1) a8 = (-3)(-27) a8 = (-3)(-128)

10 nth Term of an Geometric Sequence:
an = a1r(n – 1) Ex. 2 Determine the following: a) Find the eighth term of a geometric sequence for which a1 = -3 and r = -2. a8 = a1r(8 – 1) a8 = (-3)r(8 – 1) a8 = (-3)(-2)(8 – 1) a8 = (-3)(-27) a8 = (-3)(-128) a8 = 384

11 b) Write an equation for the nth term of the
b) Write an equation for the nth term of the geometric sequence 3, 12, 48, 192, …

12 b) Write an equation for the nth term of the
b) Write an equation for the nth term of the geometric sequence 3, 12, 48, 192, … 12 3

13 b) Write an equation for the nth term of the
b) Write an equation for the nth term of the geometric sequence 3, 12, 48, 192, … ·4

14 b) Write an equation for the nth term of the
b) Write an equation for the nth term of the geometric sequence 3, 12, 48, 192, … r = 4

15 b) Write an equation for the nth term of the
b) Write an equation for the nth term of the geometric sequence 3, 12, 48, 192, … r = 4 an = a1r(n – 1)

16 b) Write an equation for the nth term of the
b) Write an equation for the nth term of the geometric sequence 3, 12, 48, 192, … r = 4 an = a1r(n – 1) an = (3)r(n – 1)

17 b) Write an equation for the nth term of the
b) Write an equation for the nth term of the geometric sequence 3, 12, 48, 192, … r = 4 an = a1r(n – 1) an = (3)(4)(n – 1)

18 b) Write an equation for the nth term of the
b) Write an equation for the nth term of the geometric sequence 3, 12, 48, 192, … r = 4 an = a1r(n – 1) an = (3)4n – 1

19 b) Write an equation for the nth term of the
b) Write an equation for the nth term of the geometric sequence 3, 12, 48, 192, … r = 4 an = a1r(n – 1) an = (3)4n – 1 c) Find the tenth term of a geometric sequence for which a4 = 108 and r = 3.

20 b) Write an equation for the nth term of the
b) Write an equation for the nth term of the geometric sequence 3, 12, 48, 192, … r = 4 an = a1r(n – 1) an = (3)4n – 1 c) Find the tenth term of a geometric sequence for which a4 = 108 and r = 3. 1. Find a1

21 b) Write an equation for the nth term of the
b) Write an equation for the nth term of the geometric sequence 3, 12, 48, 192, … r = 4 an = a1r(n – 1) an = (3)4n – 1 c) Find the tenth term of a geometric sequence for which a4 = 108 and r = 3. 1. Find a1: an = a1r(n – 1)

22 b) Write an equation for the nth term of the
b) Write an equation for the nth term of the geometric sequence 3, 12, 48, 192, … r = 4 an = a1r(n – 1) an = (3)4n – 1 c) Find the tenth term of a geometric sequence for which a4 = 108 and r = 3. 1. Find a1: a4 = a1r(4 – 1)

23 b) Write an equation for the nth term of the
b) Write an equation for the nth term of the geometric sequence 3, 12, 48, 192, … r = 4 an = a1r(n – 1) an = (3)4n – 1 c) Find the tenth term of a geometric sequence for which a4 = 108 and r = 3. 1. Find a1: a4 = a1r(4 – 1) 108 = a1r(4 – 1)

24 b) Write an equation for the nth term of the
b) Write an equation for the nth term of the geometric sequence 3, 12, 48, 192, … r = 4 an = a1r(n – 1) an = (3)4n – 1 c) Find the tenth term of a geometric sequence for which a4 = 108 and r = 3. 1. Find a1: a4 = a1r(4 – 1) 108 = a1r(4 – 1) 108 = a13(4 – 1)

25 b) Write an equation for the nth term of the
b) Write an equation for the nth term of the geometric sequence 3, 12, 48, 192, … r = 4 an = a1r(n – 1) an = (3)4n – 1 c) Find the tenth term of a geometric sequence for which a4 = 108 and r = 3. 1. Find a1: a4 = a1r(4 – 1) 108 = a1r(4 – 1) 108 = a13(4 – 1) 108 = a133

26 b) Write an equation for the nth term of the
b) Write an equation for the nth term of the geometric sequence 3, 12, 48, 192, … r = 4 an = a1r(n – 1) an = (3)4n – 1 c) Find the tenth term of a geometric sequence for which a4 = 108 and r = 3. 1. Find a1: a4 = a1r(4 – 1) 108 = a1r(4 – 1) 108 = a13(4 – 1) 108 = a133 108 = 27a1

27 b) Write an equation for the nth term of the
b) Write an equation for the nth term of the geometric sequence 3, 12, 48, 192, … r = 4 an = a1r(n – 1) an = (3)4n – 1 c) Find the tenth term of a geometric sequence for which a4 = 108 and r = 3. 1. Find a1: a4 = a1r(4 – 1) 108 = a1r(4 – 1) 108 = a13(4 – 1) 108 = a133 108 = 27a1 4 = a1

28 c)Find the tenth term of a geometric
c)Find the tenth term of a geometric sequence for which a4 = 108 and r = 3. 1. Find a1: a4 = a1r(4 – 1) 108 = a1r(4 – 1) 108 = a13(4 – 1) 108 = a133 108 = 27a1 4 = a1 2. Now use a1 = 4 and r = 3 to find a10

29 c)Find the tenth term of a geometric
c)Find the tenth term of a geometric sequence for which a4 = 108 and r = 3. 1. Find a1: a4 = a1r(4 – 1) 108 = a1r(4 – 1) 108 = a13(4 – 1) 108 = a133 108 = 27a1 4 = a1 2. Now use a1 = 4 and r = 3 to find a10 an = a1r(n – 1)

30 c)Find the tenth term of a geometric
c)Find the tenth term of a geometric sequence for which a4 = 108 and r = 3. 1. Find a1: a4 = a1r(4 – 1) 108 = a1r(4 – 1) 108 = a13(4 – 1) 108 = a133 108 = 27a1 4 = a1 2. Now use a1 = 4 and r = 3 to find a10 an = a1r(n – 1) a10 = a1r(10 – 1)

31 c)Find the tenth term of a geometric
c)Find the tenth term of a geometric sequence for which a4 = 108 and r = 3. 1. Find a1: a4 = a1r(4 – 1) 108 = a1r(4 – 1) 108 = a13(4 – 1) 108 = a133 108 = 27a1 4 = a1 2. Now use a1 = 4 and r = 3 to find a10 an = a1r(n – 1) a10 = a1r(10 – 1) a10 = (4)r(10 – 1)

32 c)Find the tenth term of a geometric
c)Find the tenth term of a geometric sequence for which a4 = 108 and r = 3. 1. Find a1: a4 = a1r(4 – 1) 108 = a1r(4 – 1) 108 = a13(4 – 1) 108 = a133 108 = 27a1 4 = a1 2. Now use a1 = 4 and r = 3 to find a10 an = a1r(n – 1) a10 = a1r(10 – 1) a10 = (4)r(10 – 1) a10 = (4)(3)(10 – 1)

33 c)Find the tenth term of a geometric
c)Find the tenth term of a geometric sequence for which a4 = 108 and r = 3. 1. Find a1: a4 = a1r(4 – 1) 108 = a1r(4 – 1) 108 = a13(4 – 1) 108 = a133 108 = 27a1 4 = a1 2. Now use a1 = 4 and r = 3 to find a10 an = a1r(n – 1) a10 = a1r(10 – 1) a10 = (4)r(10 – 1) a10 = (4)(3)(10 – 1) a10 = (4)(39)

34 c)Find the tenth term of a geometric
c)Find the tenth term of a geometric sequence for which a4 = 108 and r = 3. 1. Find a1: a4 = a1r(4 – 1) 108 = a1r(4 – 1) 108 = a13(4 – 1) 108 = a133 108 = 27a1 4 = a1 2. Now use a1 = 4 and r = 3 to find a10 an = a1r(n – 1) a10 = a1r(10 – 1) a10 = (4)r(10 – 1) a10 = (4)(3)(10 – 1) a10 = (4)(39) a10 = (4)(19,683)

35 c)Find the tenth term of a geometric sequence for
c)Find the tenth term of a geometric sequence for which a4 = 108 and r = 3. 1. Find a1: a4 = a1r(4 – 1) 108 = a1r(4 – 1) 108 = a13(4 – 1) 108 = a133 108 = 27a1 4 = a1 2. Now use a1 = 4 and r = 3 to find a10 an = a1r(n – 1) a10 = a1r(10 – 1) a10 = (4)r(10 – 1) a10 = (4)(3)(10 – 1) a10 = (4)(39) a10 = (4)(19,683) a10 = 78,732

36 Sum of a Geometric Series
The sum Sn of the first n terms of a geometric series is given by the following: Sn = a1(1 – r n) 1 – r

37 Sum of a Geometric Series
The sum Sn of the first n terms of a geometric series is given by the following: Sn = a1(1 – r n) 1 – r Ex. 3 Find the sum of the first 15 terms of the geometric sequence in which a1 = 2 and r = 2.

38 Sum of a Geometric Series
The sum Sn of the first n terms of a geometric series is given by the following: Sn = a1(1 – r n) 1 – r Ex. 3 Find the sum of the first 15 terms of the geometric sequence in which a1 = 2 and r = 2.

39 Sum of a Geometric Series
The sum Sn of the first n terms of a geometric series is given by the following: Sn = a1(1 – r n) 1 – r Ex. 3 Find the sum of the first 15 terms of the geometric sequence in which a1 = 2 and r = 2. S15 = a1(1 – r15)

40 Sum of a Geometric Series
The sum Sn of the first n terms of a geometric series is given by the following: Sn = a1(1 – r n) 1 – r Ex. 3 Find the sum of the first 15 terms of the geometric sequence in which a1 = 2 and r = 2. S15 = a1(1 – r15) S15 = 2(1 – r15)

41 Sum of a Geometric Series
The sum Sn of the first n terms of a geometric series is given by the following: Sn = a1(1 – r n) 1 – r Ex. 3 Find the sum of the first 15 terms of the geometric sequence in which a1 = 2 and r = 2. S15 = a1(1 – r15) S15 = 2(1 – r15) S15 = 2(1 – 215) 1 – 2

42 Sum of a Geometric Series
The sum Sn of the first n terms of a geometric series is given by the following: Sn = a1(1 – r n) 1 – r Ex. 3 Find the sum of the first 15 terms of the geometric sequence in which a1 = 2 and r = 2. S15 = a1(1 – r15) S15 = 2(1 – r15) S15 = 2(1 – 215) 1 – 2 S15 = 2(1 – 215) = 2(1 – 32,768) 1 –

43 Sum of a Geometric Series
The sum Sn of the first n terms of a geometric series is given by the following: Sn = a1(1 – r n) 1 – r Ex. 3 Find the sum of the first 15 terms of the geometric sequence in which a1 = 2 and r = 2. S15 = a1(1 – r15) S15 = 2(1 – r15) S15 = 2(1 – 215) 1 – 2 S15 = 2(1 – 215) = 2(1 – 32,768) = -65,534 1 –

44 Sum of a Geometric Series
The sum Sn of the first n terms of a geometric series is given by the following: Sn = a1(1 – r n) 1 – r Ex. 3 Find the sum of the first 15 terms of the geometric sequence in which a1 = 2 and r = 2. S15 = a1(1 – r15) S15 = 2(1 – r15) S15 = 2(1 – 215) 1 – 2 S15 = 2(1 – 215) = 2(1 – 32,768) = -65,534 = 65,534 1 –


Download ppt "11.3: Geometric Sequences & Series"

Similar presentations


Ads by Google